"Set your minds on things above": shifting from trauma-based ruminations to ruminating on God - Knabb, Joshua (Mental health, religion & culture, 2019)
In this study, the authors investigated the relationship between trauma-based "Christian rumination," mindfulness, and focusing on God among an online sample of Christian adults (N = 234) from the United States. Participants endorsed experiencing a range of traumatic events, including natural disasters, car accidents, the death of loved ones, assault, and abuse, as well as the tendency to continue to think about the event. Using structural equation modelling, results revealed that "Christian rumination," consisting of trauma-related ruminations (e.g., "why" and "what if" questions about the traumatic event, questioning God’s availability in the midst of the traumatic event), was positively associated with attempts to focus on God as a form of religious coping, mediated by mindfulness skills (i.e., attention, present focus, awareness, acceptance). The authors conclude by discussing a manualized treatment approach in development, based on the empirically-confirmed theoretical model in the present study, along with study limitations.